Clinical analysis of bronchoscope diagnosis and treatment for airway foreign body removal in pediatric patients - Lin-Lin Han; Chen Meng; Zhong-Xiao Zhang; Xiao-Di Tang; Jing Ma; Chang-Xiao Li (BMC, 2022)
Abstract Background Along with the wide spread application and technical development of the flexible and rigid bronchoscopy, the airway foreign body removing method cme to the specific technique for different foreign bodies from the single foreign body forceps. Methods Selected 633 children who were diagnosed as airway foreign bodies by the Department of Respiratory Intervention, Children's Hospital affiliated to Shandong University from January 1st, 2018 to December 31st, 2021, and the airway foreign bodies were diagnosed using bronchoscopy. After comprehensive assessment of the foreign body nature in the airway, the foreign bodies were removed by freezing, laser, electrocoagulation, balloon and other techniques, the success rate of the foreign body removed from the airway was observed, the percentage of the foreign body removed using different techniques, the operation time, and the incidence of post-adverse reactions during operation. Results The success rate using flexible bronchoscope alone to remove foreign bodies in the airway was 99.2%. After flexible bronchoscopy, 19 cases of foreign bodies were removed by vacuum suction alone, 513 cases were removed by foreign body forceps alone, 62 cases were combined with cryotherapy, 2 cases were electrocoagulation, 6 cases were mesh baskets, 3 cases were balloons, 5 cases were laser, and various 18 cases of foreign bodies were invloved by technical combination. 5 cases of flexible bronchoscope combined with rigid bronchoscope combined to remove foreign bodies. The operation time was from 5 min to 1 h, with an average of 20 min. There were 17 cases of hypoxemia (2.7%) during operation, 36 cases (5.7%) of bleeding caused by airway mucosa injury after treatment, and 70 cases (11.2%) of laryngeal edema. The total incidence of adverse reactions was 19.6%, there were no deaths due to foreign bodies and treatment. Conclusions According to different properties of airway foreign bodies, it is safe and effective to select appropriate techniques to remove foreign bodies using the flexible bronchoscope, which can increase the removal rate of airway foreign bodies and reduce the occurrence of serious complications.